Pain Management in Nursing Home Residents: Findings from a Pilot Effectiveness‐Implementation Study. Issue 12 (27th August 2019) - Brunkert, Thekla; Simon, Michael; Ruppen, Wilhelm; Zúñiga, Franziska
Abstract : OBJECTIVES: To evaluate the effectiveness and implementation of a multilevel pain management intervention in nursing homes (NHs) comprising a pain management guideline, care worker training, and pain champions. DESIGN: An implementation science pilot study using a quasi‐experimental effectiveness‐implementation (hybrid II) design. SETTING: Four NHs in Switzerland. PARTICIPANTS: All consenting long‐term residents aged 65 years and older with pain at baseline (N = 62) and all registered and licensed practical nurses (N = 61). INTERVENTION: Implementation of a contextually adapted pain management guideline, interactive training workshops for all care workers, and specifically trained pain champions. MEASUREMENTS: Interference from pain, worst and average pain intensity over the previous 24 hours; proxy ratings of pain with the Pain Assessment in Advanced Dementia scale; and care workers' appraisal of the guideline's reach, acceptability, and adoption. RESULTS: Pain‐related outcomes improved for self‐reporting residents (n = 43) and residents with proxy rating (n = 19). Significant improvements of average pain from baseline to T1 ( P = .006), and in worst pain from baseline to T1 ( P = .003) and T2 (P = .004). No significant changes in interference from pain ( P = .18). With regard to the implementation efforts, about 76% of care workers indicated they were familiar with the guideline; 70.4% agreed that the guideline is practical and matches their ideas of good pain assessment (75.9%) and treatment (79.7%). CONCLUSION: Implementation of a multilevel pain management intervention did significantly improve average and worst pain intensity in NH residents. However, to effect clinical meaningful changes in interference from pain, a more comprehensive approach involving other disciplines may be necessary. J Am Geriatr Soc 67:2574–2580, 2019